Propafenone efficacy in treatment of atrial fibrillation paroxysms: a placebo-controlled study - Yu. A. Bunin; L. K. Anfalova (Российский кардиологический журнал, 2005)
In a placebo-controlled study, propafenone efficacy and safety for pharmaceutical cardioversion in atrial fibrillation (AF) paroxysms were studied. The study included 50 patients aged 28-69 years (mean age 53,9+9,7), with AF paroxysms lasting for less than 48 hours. Participants were randomized to propafenone (single dose of 600 mg, per os) or placebo. Eight hours later, sinus rhythm was restored in propafenone group more effectively than in placebo group: 85,7% and 33,3%, respectively (p=0,001). Mean sinus rhythm restoring time was 2,5+1,9 and 3,8+1,5 hours, respectively.